Readiness of Christian Religious Education (CRE) Teachers and Implementation of Competence-Based Curriculum (CBC) in Nyakabande Sub-county Kisoro District. - Mugwaneza, Allen (Kabale University, 2024)
The Competence-Based Curriculum (CBC) introduced in Uganda marks a significant shift in the educational landscape, prioritizing the development of practical skills and competencies over traditional knowledge acquisition. This transformative approach requires a corresponding change in teaching methodologies, particularly in subjects like Christian Religious Education (CRE). This study examines the readiness of CRE teachers in Nyakabande Sub-county, Kisoro District, to implement the CBC, addressing critical questions about their preparedness, the challenges they face, and potential strategies for improvement. Motivated by the need to understand the specific difficulties CRE teachers encounter during the transition to CBC, this research explores the implications of adopting learner-centered teaching methods, critical thinking, and real-world knowledge application. Despite the CBC’s promise of enhancing educational outcomes, its implementation has been challenged by factors such as insufficient teacher training, limited resources, and resistance to departing from traditional teaching practices. A descriptive research design was employed, incorporating both quantitative and qualitative methods to provide a comprehensive assessment. The study targeted CRE teachers, school administrators, and education officers within Nyakabande Sub-county. Stratified random sampling ensured a diverse representation of participants from various school types. The findings of this study reveal the current state of preparedness among CRE teachers and identify specific obstacles hindering the effective implementation of CBC. Moreover, the study offers practical recommendations to enhance teacher readiness, aiming to improve the overall efficacy of CBC in religious education. By addressing these critical issues, this research contributes to the broader objective of aligning Uganda’s educational practices with global standards, ultimately fostering better educational outcomes.